Weathering the Storms? Minimum-Income Benefits as a Crisis Response - Herwig Immervoll; Felizia Pasteiner (Institute of Labor Economics (IZA), 2025)
Economic crises produce rapid and sizable shifts in the demand for social support. Means-tested cash transfers, such as 'social assistance' programmes and related minimum-income benefits (MIB) typically function as benefits of last-resort, filling some of the support gaps left by other government transfers and are key pillars of strategies to alleviate hardship and prevent long-term damage from episodes spent in poverty. This paper discusses crisis-related challenges for MIB programmes, focussing on support for working-age individuals and their families, and drawing on the experience of OECD countries during the COVID-19 pandemic and the subsequent cost-of-living crisis. It compares MIB provisions before these crises, surveys countries' approaches and reforms in subsequent years, and distils lessons for making MIBs more effective, responsive and crisis ready.
Keywords: H53; H31; D31; I38; H12; E66; 330; minimum-income benefits; social assistance; economic crisis; COVID-19; inflation; poverty